Powerful Women, Men in Power: An Analysis of Kösem Sultan and Lady Macbeth - Kadriye Bozkurt (Akademik İncelemeler Dergisi)
There has been an intricate relationship and interconnectedness between gender and power/authority throughout human culture and history. From the male rulers of kingdoms to the male leaders of nations, the power dynamic has been structured around male participation, with various forms of power in the hands of men. Two powerful fictional female characters created in Turkish and English literature, A. Turan Oflazoğlu’s Kösem Sultan and William Shakespeare’s Lady Macbeth, will be analysed in this study to reflect the distribution of power by gender. These two strong female characters at the centre of this study, are remarkable for their intelligence, ambition and lust for power. Since the qualities associated with incompletion and fragility are ascribed to women, they have only indirectly come to power because they are not men. By considering the practices that are effective in social and political life such as the sultanate system and the great chain of being in the fictional periods in which the plays are set, the link between the concept of power and gender will be revealed. The relationship between power and gender will also be evaluated in the context of Simone de Beauvoir's ideas on male domination and Michel Foucault's ideas on power, as they have a significant impact on the perception of power and gender in today’s societies. Therefore, this study will highlight the relationship of power dynamics with gender issues through the analysis of the plays Kösem Sultan and Macbeth by referring to the ideas of Foucault and Beauvoir.